2020
DOI: 10.1155/2020/4145164
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Immune Infiltrates of ABCA8 and FABP4 in Stomach Adenocarcinoma

Abstract: Background. Stomach adenocarcinoma (STAD) is a common malignancy worldwide with poor prognosis. Therefore, it is important to identify a valuable prognostic biomarker for STAD. The aim of present study was to identify novel prognostic biomarkers for STAD and evaluate the potential role of hub genes in STAD. Methods. Gene Expression Profiling Interactive Analysis (GEPIA) and Cancer RNA-Seq Nexus were performed to identify differentially expressed genes (DEGs). Subsequently, hub genes were selected by a Venn dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
(55 reference statements)
1
17
0
Order By: Relevance
“…Although the research on PAAD has advanced greatly in terms of early diagnosis, surgical technique, and drug treatment in recent years, the prognosis of PAAD remains poor ( Rawla et al, 2019 ; Yao et al, 2019 ; Zhang et al, 2019 ). Reducing the mortality of PAAD patients and improving their early diagnosis and prognosis urgently require understanding the effects of early-stage gene expression and immune cell infiltration on prognosis ( Chou et al, 2016 ; Guo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the research on PAAD has advanced greatly in terms of early diagnosis, surgical technique, and drug treatment in recent years, the prognosis of PAAD remains poor ( Rawla et al, 2019 ; Yao et al, 2019 ; Zhang et al, 2019 ). Reducing the mortality of PAAD patients and improving their early diagnosis and prognosis urgently require understanding the effects of early-stage gene expression and immune cell infiltration on prognosis ( Chou et al, 2016 ; Guo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with our qRT-PCR and microarray results showing that the expression level of ABCA8 was significantly decreased in the CS invasive group vs. the non-invasive group. Guo et al (2020) found that the increased expression of ABCA8 is correlated with poor prognosis and is associated with immune infiltration in stomach adenocarcinoma. Glypican-3 (GPC3) is a cell surface proteoglycan anchored by glycosyl-phosphatidylinositol ( Pilia et al, 1996 ).…”
Section: Discussionmentioning
confidence: 93%
“…39 In addition, ABCA8 inhibits progression of prostate cancer, but promotes the progression of stomach adenocarcinoma. 40,41 We have not found any studies on the regulation of LUAD progression or inflammation by ABCA8. Previous studies have shown that ADAM metallopeptidase with thrombospondin type 1 motif 8 (ADAMTS8) was downregulated in non-small cell lung cancer, which is consistent with our results.…”
mentioning
confidence: 93%